ANALISIS KINERJA SIMPANG EMPAT TRUNOJOYO – KH. SAJAD – DR. WAHIDIN KABUPATEN SUMENEP MENGGUNAKAN PERANGKAT LUNAK PTV VISTRO - Nugraha, Nur Aryasatya; Hidayati, Lydia Novitriana Nur; Yulianto, Budi (Jurnal Riset Rekayasa Sipil, 2025)
Intersection Four Trunojoyo - KH. Sajad - Dr. Wahidin are intersections included in the Trunojoyo road network. Intersection Four Trunojoyo - KH Sajad - Dr. Wahidin is a newly implemented intersection because it was not an intersection five years ago. The research aims to analyse the performance of the signalised intersection at the Trunojoyo - KH Sajad - Dr. Wahidin. The study analysis used PTV Vistro software. The modelling method refers to HCM 2010. Modelling is done with two scenarios: existing and locally optimised conditions. After modelling the existing conditions, validation is carried out through queue length using Microsoft Excel software. There is an increase in performance modelling when a single optimisation scenario and vehicle actuated is carried out compared to existing conditions. In the existing conditions, the Trunojoyo - KH. In the morning peak hour, Sajad - Dr. Wahidin Interchange produces a DS value = 0.39, D = 34.52 seconds /mp, and the afternoon peak hour DS value = 0.41 and D = 38.59. The best optimisation performance is in the vehicle actuated optimisation type scheme 1, with an extension time of 2 seconds. The intersection of Trunojoyo - KH. Sajad - Dr. Wahidin has a degree of saturation (DS) = 0.34 and delay = 19.4 sec/smp in the morning peak hour, while the afternoon peak hour produces a degree of saturation (DS) = 0.41 and delay = 21.18 sec/smp. The use of detectors in PTV Vistro modeling can improve intersection performance, followed by the appropriate setting of other signal parameters.